INFLUENCE OF THE DIFFERENT KINDS DAIRY RAW TO THE DEVELOPMENT OF THE OPPORTUNISTIC PATHOGENIC MICROFLORA - Maria Kosenko; Irina Kulikova (Вестник Северо-Кавказского федерального университета, 2022)
Lactic acid bacteria have long history of application in fermented foods as a starter cultures to produce dairy, meat and bakery because of their beneficial influence on nutritional, organoleptic, and shelf-life characteristics. Lactic acid bacteria are also known to produce and excrete compounds with antimicrobial activity, such as hydrogen peroxide, carbon dioxide, diacetyl, bacteriocins and bacteriocin like substances. All antimicrobial compounds can antagonize the growth of some spoilage and pathogenic bacteria in foods and have been explored in the control of most unwanted organisms.